A modular approach to neutral P,N-ligands: synthesis and coordination chemistry - Vasilenko, Vladislav; Roth, Torsten; Blasius, Clemens K.; Intorp, Sebastian N.; Wadepohl, Hubert; Gade, Lutz H. (Beilstein Journal of Organic Chemistry, 2016)
We report the modular synthesis of three different types of neutral κ2-P,N-ligands comprising an imine and a phosphine binding site. These ligands were reacted with rhodium, iridium and palladium metal precursors and the structures of the resulting complexes were elucidated by means of X-ray crystallography. We observed that subtle changes of the ligand backbone have a significant influence on the binding geometry und coordination properties of these bidentate P,N-donors.
Keywords: P,N-ligands; phosphanylformamidines; phosphine imines; transition metal complexes